Extraction and identification of durian’s volatile: a review - Lim, Soo Chin; Juhari, Nurul Hanisah; Ola, Lasekan; Pak Dek, Mohd Sabri; Nik Hadzir, Noor Hadzuin (American Chemical Society (ACS), 2025)
Durian is a climacteric fruit known as the “king of tropical fruits”. The strong, intense durian flavor is controversial, as many cannot accept the distinct sulfurous odor described. The durian aroma is mainly attributed to the volatile compounds. This review paper concludes the overview and contribution of volatile compounds to the durian flavor. Extraction and identification methods used from different literature are also summarized. Esters and sulfur compounds are the two predominant volatile compounds, with sulfur compounds responsible for the distinct strong onion-like odor and esters possessing the fruity odor in the fruit. The key esters in durians are ethyl 2-methyl butanoate, propyl 2-methyl butanoate, or ethyl propanoate, whereas diethyl disulfide, diethyl trisulfide, and 3,5-dimethyl-1,2,4-trithiolane are found in durian as predominant sulfur-containing volatiles. Alcohols, aldehydes, and ketones are also found in a relatively smaller proportion. By providing a comprehensive overview of durian’s volatile composition and analytical approaches, this review serves as a valuable reference for researchers, food scientists, and the food industry in furthering the understanding of durian aroma and improving its quality assessment, breeding, and postharvest handling.